Cuidados al paciente pediátrico con COVID – 19 en el ámbito hospitalario y comunitario - Nadia Lizeth, Pasquel Mora (2021)
COVID-19 is an infectious disease caused by the SARS-CoV-2 virus, which was declared a pandemic by the World Health Organization (WHO) on April 17, 2020, when 1,250,000 confirmed cases were reported, approximately in 180 countries and 69,210 deaths, generating a mortality rate of 5.5% worldwide. The purpose of this investigation is proposing nursing care that should be provided to pediatric patients with this pathology in order to offer specialized care in both the community and hospital areas, using the information on general recommendations. A bibliographic review was carried out, conducting a search in scientific databases such as the Virtual Health Library, Centers for Disease Control Prevention (CDC), Scopus, Pubmed, Academic Google and official websites of corporate authors experts in the área, the World Health Organization, Pan American Health Organization, National Institute of Statistics and Censuses (Ecuador) and the Ministry of Public Health of Ecuador. Of which 106 documents that met the inclusion criteria were selected. Trought gathered information was created a matrix that reflects the similarities and differences described by various authors, focused on care recommendations in pediatric patients with COVID-19, proposing a specific nursing care plan for their care.